1965
DOI: 10.1111/j.1537-2995.1965.tb01146.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dextran on Platelet Factor 3 Activity: In Vitro and In Vivo Studies

Abstract: Intravenous infusions of one liter of low molecular weight and standard clinical dextran in normal adult subjects resulted in a significant alteration of platelet function as characterized by marked depression of platelet factor 3 (PF 3) activity. Disruption of the abnormal platelets by sonic oscillation corrected the defect, indicating that dextran coating of the platelets inhibited the release of PF 3 activity. These findings were confirmed by in vitro studies. Infusions of serum albumin failed to produce a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1966
1966
1992
1992

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Dextran 40 inhibited platelet adhesion and aggregation, possibly due to depressed plasma factor VIII activity [1]. Dextran formed a monomolecular layer on the platelet surface, which resulted in a marked decrease of platelet factor III (PF3) activity [10,27]. Ultrastructural studies [34] displayed that dextran macromolecules formed bridges between the adjacent platelet membranes, thus inducing aggregation due to absorption forces.…”
Section: Discussionmentioning
confidence: 97%
“…Dextran 40 inhibited platelet adhesion and aggregation, possibly due to depressed plasma factor VIII activity [1]. Dextran formed a monomolecular layer on the platelet surface, which resulted in a marked decrease of platelet factor III (PF3) activity [10,27]. Ultrastructural studies [34] displayed that dextran macromolecules formed bridges between the adjacent platelet membranes, thus inducing aggregation due to absorption forces.…”
Section: Discussionmentioning
confidence: 97%
“…It has been demonstrated that infusions of dextran alter some functional properties of the platelets, such as the release of platelet factor 3 (Ewald et al 1965), resistance to ultrasonic disruption (Brewer 1964) and electrophoretic mobility (Ross and Ebert 1959). It is therefore interesting that the physiological activity of the platelet represented by the spreading capacity was not influenced by the experimentally reached concentrations of dextran.…”
Section: Discussionmentioning
confidence: 99%
“…The most common drugs interfering with platelet membrane function or receptors are amitriptyline (Elavil), 123 imipramine (Tofranil), 124 doxepin (Sinequan), 125 chlorpromazine (Thorazine), 126 cocaine, 127 lidocaine (Xylocaine), 128 isoproterenol (Isuprel), 129 propranolol, 130 cephalothin (Keflin), 131 ampicillin, 132 carbenicillin, 133 penicillin, 134 diphenhydramine (Benadryl), 135 promethazine (Phenergan), 136 and alcohol. Other drugs inducing platelet dysfunction by this mechanism are phentolamine (Regitine), 137 phenoxybenzamine (Dibenzyline), 137 reserpine, 138 dihydroergotamine, 139 desipramine (Norpramine), 124 nortryptyline (Aventyl), 124 trifluoroperazine (Stelazine), 140 procaine, 140 dibucaine (Nupercaine), 141 nitrofurantoin (Furadantin), 142 nafcillin, 143 moxalactam, 144 ticarcillin, 145 dextran, 146 and hydroxyethyl starch. 147…”
Section: Drugs Interfering With Platelet Membrane Receptorsmentioning
confidence: 99%